Molecular epidemiological investigation and recombination analysis of Cachavirus prevalent in China - Leng, Chaoliang; Tian, Xiang; Zhai, Hongyue; Ji, Jun; Yao, Lunguang (Frontiers in Veterinary Science, 2024)
Chaphamaparvovirus carnivoran1 (canine chaphamaparvovirus, also known as Cachavirus [CachaV]) is a novel parvovirus first reported in dog feces collected from the USA in 2017 and China in 2019. To continuously track its infection and evolution status, 276 canine anal swabs were obtained from pet hospitals in central, northern, and eastern China between 2021 and 2023 and screened via polymerase chain reaction; subsequently, a systematic study was conducted. Of these samples, nine (3.3%) were positive for CachaV. Using polymerase chain reaction, whole genome sequences of the nine CachaV-positive strains were amplified. The NS1 amino acid sequence identity between CachaV strains from China and other countries was 96.23%-99.85%, whereas the VP1 protein sequence identity was 95.83%-100%. CHN230521 demonstrated the highest identity for NS1 amino acids (99.85%) and VP1 amino acids (100%) with NWT-W88 and CP-T015. According to the model prediction of CHN220916-VP1 protein, Met64Thr, Thr107Ala, and Phe131Ser mutations may cause tertiary structural changes in VP1 protein. Interestingly, each of the nine CachaV strains harbored the same site mutations in NS1 (Ser252Cys, Gly253Leu, and Gly254Thr). Although no explicit recombination events were predicted, the clustering and branching of the phylogenetic tree were complicated. Based on the evolution trees for VP1 and NS1, the nine CachaV strains identified from 2021 to 2023 were closely related to those identified in gray wolves and cats. This study may be beneficial for evaluating the prevalence of CachaVs in China, thereby understanding the evolution trend of CachaVs.